1983
DOI: 10.1007/bf00196189
|View full text |Cite
|
Sign up to set email alerts
|

The formation of solar prominences by magnetic reconnection and condensation

Abstract: A model for solar quiescent prominences nested in a ' Figure 8' magnetic field topology is developed. This topology is argued to be the natural consequence of the distention of bipolar regions upward into the corona. If this distention is slow enough so that hydrostatic equilibrium holds approximately along the field lines, the transverse gas pressure forces fall exponentially with height whereas the inward Lorentz forces fall as a power law. At a low height in the corona, the pressure forces cannot balance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 24 publications
0
54
0
Order By: Relevance
“…Such force-free fields can contain dips in the field lines even when the underlying photospheric field is dipolar. In fact, many authors have suggested that filaments are supported by nearly force-free flux ropes that lie horizontally above the PIL (e.g., Kuperus and Raadu, 1974;Pneuman, 1983;van Ballegooijen and Martens, 1989;Rust and Kumar, 1994;). An alternative force-free configuration with dips, the sheared arcade, has also been studied as a description of the filament channel magnetic structure (Antiochos et al, 1994;DeVore and Antiochos, 2000;.…”
Section: Models Of Prominence Magnetic Structurementioning
confidence: 99%
“…Such force-free fields can contain dips in the field lines even when the underlying photospheric field is dipolar. In fact, many authors have suggested that filaments are supported by nearly force-free flux ropes that lie horizontally above the PIL (e.g., Kuperus and Raadu, 1974;Pneuman, 1983;van Ballegooijen and Martens, 1989;Rust and Kumar, 1994;). An alternative force-free configuration with dips, the sheared arcade, has also been studied as a description of the filament channel magnetic structure (Antiochos et al, 1994;DeVore and Antiochos, 2000;.…”
Section: Models Of Prominence Magnetic Structurementioning
confidence: 99%
“…Previous findings about prominence magnetic structure have shown models with dipped field lines in a normal (Kippenhahn & SchlĂŒter 1957) or inverse 1 (Kuperus & Raadu 1974;Pneuman 1983) polarity configuration, the latter having a helical structure. From a large sample of quiescent prominence observations, Leroy et al (1984) found both types of configurations and a strong correlation between the magnetic field topology and the height of the prominence.…”
Section: Introductionmentioning
confidence: 95%
“…On the one hand, there is the sheared arcade model that, by large-scale photospheric footpoint motions (such as shear at, and convergence towards the PIL, and subsequent reconnection processes), is able to form dips and even helical structures, where plasma can be gravitationally confined (e.g., Pneuman 1983;van Ballegooijen & Martens 1989;Antiochos et al 1994;Aulanier & Demoulin 1998;DeVore & Antiochos 2000;Martens & Zwaan 2001;Welsch et al 2005;Karpen 2007). This model is capable of reproducing both inverse and normal polarity configurations in the same filament (Aulanier et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several different models have been suggested to explain how cool, dense objects like prominences can be supported in and thermally isolated from the surrounding hot, tenuous coronal plasma (e.g., Tandberg-Hanssen 1995), and these models generally fall into one of two main categories: dip models (Kippenhahn & SchlĂŒter 1957;Antiochos & Klimchuk 1991), and flux-rope models (Hirayama 1985;Leroy 1989;Kuperus & Raadu 1974;Pneuman 1983;Anzer 1989; see also Fig. 1).…”
Section: Introductionmentioning
confidence: 99%